Pulmonary involvement in rheumatoid arthritis (1995)
Pulmonary involvement is one of the extra-articular manifestations of rheumatoidarthritis (RA) and includes pleurisy, parenchymal nodules, interstitial involvement, and airway disease. Rheumatoid pulmonary vasculitis is rare. Pulmonary disease also may be observed as a toxic event consequent to treatment for RA. Although RA is more common in women, rheumatoid lung disease occurs more frequently in men who have long-standing rheumatoid disease, positive rheumatoid factor and subcutaneous nodules. Pleural involvement, usually asymptomatic, is the most common manifestation of lung disease in RA and may occur concurrently with pulmonary nodulosis or interstitial disease. The clinical features and course of pulmonary fibrosis in RA are similar to those of idiopathic pulmonary fibrosis. Bronchiolitis obliterans organizing pneumonia (BOOP), which has been recently described in RA patients, has nonspecific clinical features. The histological patterns correspond to proliferative bronchiolitis in the airway and organizing pneumonia in the alveoli. Obstructive lung disease in RA includes obliterative bronchiolitis (0B) and bronchiectasis. OB is an acute illness characterized histologically by a constrictive bronchiolitis. It may be idiopathic or induced by D-penicillamine or intramuscular gold compounds. Methotrexate (MTX)-pneumonitis is an uncommon complication of MTX treatment. Its clinical presentation is not specific, and diagnosis must be made after exclusion of other causes of pulmonary diseases. It is uncertain if preexisting lung disease predisposes RA patients to MTX-pneumonitis. Treatment of lung disease in RA is empirical. Corticosteroids are usually administered and immunosuppressive drugs are often added when pulmonary disease progresses and/or steroid side-effects appear.